Association of APC gene promoter methylation and the risk of gastric cancer: A meta-analysis and bioinformatics study. Issue 16 (April 2020) - Zhou, Xueliang; Jiao, Dechao; Dou, Mengmeng; Zhang, Weijie; Hua, Hao; Chen, Jianjian; Li, Zhaonan; Li, Lifeng; Han, Xinwei
Abstract: Background: The methylation status of the adenomatous polyposis coli (APC) promoter has been shown to be associated with the occurrence of gastric cancer, but this finding remains controversial. The aim of this study was to investigate the relationship between methylation of the APC gene promoter and gastric cancer. Methods: We searched the Web of Science, EMBASE, Medline, and Cochrane Central Register of Controlled Trials (CENTRAL) databases from the date of creation until August 1, 2019. According to the inclusion criteria, the relationship between the methylation status of the APC gene promoter and gastric cancer was investigated. The incidence of APC promoter methylation in the tissues or blood of patients with and without gastric cancer was compared. The results are expressed as the odds ratio (OR) and 95% confidence interval (CI). The pooled OR of each study was estimated using a fixed effects model or a random effects model to generate forest plots. We further validated the results using the MethHC database. Results: Eight studies (985 samples) were included. Our meta-analysis showed that the incidence of APC promoter methylation in patients with gastric cancer was higher than that of patients without gastric cancer (OR = 3.86, 95% CI 1.71–8.74, P = .001). Methylation of the APC promoter is associated with the incidence of gastric cancer, and it increases the risk of gastric cancer. Conclusion: This study provides a new strategic direction for research on gastric cancer. Methylation of the APC promoter may be a potential biomarker for the diagnosis of gastric cancer, but the results of this work require further confirmation. Abstract : Supplemental Digital Content is available in the text